Acupressure Reducing the Insomnia Disorders of Perimenopause - Levi Tina Sari; Ita Noviasari; Ika Agustina; Wahyu Wibisono (Journal of Ners and Midwifery, 2024)
There are two therapeutic methods for treating insomnia in perimenopause, namely chemical and complementary treatment methods. One of the complementary therapies for reducing the problem of insomnia in perimenopause is acupressure. The design of the research used a pre-experimental with one group pretest-posttest. A pretest was conducted before the treatment of giving acupressure. The population was 32 perimenopause women registered at the Jatinom elderly posyandu in Kecamatan Kanigoro Kabupaten Blitar area. The researchers calculated the sample size using the Slovin formula at a 5% confidence level resulting in a sample size of 30 people. Purposive sampling was used as the sampling technique. The analysis was carried out to see the effect of acupressure massage therapy on insomnia in perimenopause women, using the paired sample t-test. The result of this research revealed that there was a significant difference in insomnia scores before and after acupressure treatment in reducing insomnia in perimenopause women. The treatment of Acupressure was effective in reducing the insomnia disorders of perimenopause. It is suggested that perimenopause women to apply this method to reduce their insomnia since it can be done independently.